Investigation of biological factors influencing the placental mRNA profile in maternal plasma. (10th January 2014) - Tsui, Nancy B. Y.; Wong, Cesar S. C.; Chow, Katherine C. K.; Lo, Elena S. F.; Cheng, Yvonne K. Y.
ABSTRACT Objective Circulating placental‐derived RNA is useful for noninvasive prenatal investigation. However, in addition to placental gene expression, there are limited investigations on other biological parameters that may affect the circulating placental RNA profile. In this study, we explored two of these potential parameters. Methods We first demonstrated the existence of such biological parameters by comparing the relative levels of a panel of placental‐derived transcripts between the placentas and maternal plasma by digital PCRs. We then compared the post‐delivery clearance of the transcripts by serial plasma samples collected from pregnant women after delivery. We also studied the placental in vivo localization of the transcripts by in situ hybridization. Results There was an imperfect correlation of the transcript levels between the placentas and maternal plasma, with placenta‐specific 4 (PLAC4) mRNA showing the largest discrepancy. Although PLAC4 mRNA showed a similar clearance half‐life with other transcripts, we observed a preferential localization of PLAC4 mRNA around the villous surface. We speculated that this phenomenon might play a role in favoring the release of PLAC4 mRNA molecules into maternal plasma. Conclusion We revealed that in addition to expression levels in the placenta, other biological factors might interplay to determine the maternal plasma profile of placental‐derived RNAs. © 2013 John Wiley & Sons, Ltd.